How Should We Evaluate Outcomes for Use of Biologics in the Knee? - LaPrade, Christopher M.; James, Evan W.; LaPrade, Robert F.; Engebretsen, Lars (The Journal of Knee Surgery, 2015)
In recent years, the use of biologics for the primary treatment and augmentation of treatment in patients with knee pathology has increased substantially. Techniques and applications for biologic preparations such as platelet-rich plasma (PRP) and mesenchymal stem cells (MSCs) have been developed and refined to increase the healing response in bone, ligaments, cartilage, meniscal tissue, and other areas of the knee. Beginning with basic science and animal models, and finally proceeding to clinical human trials, the effect of biologics on clinical outcomes has been widely studied; however, many results have been inconclusive on their true effectiveness. The purpose of this article is to review current strategies for evaluating outcomes after biologic treatment and to propose new recommendations for assessing outcomes following the use of biologics in the knee. In addition, the importance of study design, current challenges, and future directions will be reviewed to describe the current standards for future studies to follow.
Keywords: outcomes; biologics; knee; platelet-rich plasma; mesenchymal stem cells